2020
DOI: 10.1007/s10804-020-09363-z
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Times of Economic Boom and Bust: A Narrative Study of a Rural Population Dependent upon the Oil and Gas Industry

Abstract: How do residents of small towns that depend on oil and gas extraction or processing industries withstand economic boom and bust cycles? To answer this question, this article reports on a narrative analysis of residents’ life stories gathered from 37 adults of a small town on the Canadian prairies dependent on the oil and gas industry, employing the theories of narrative inquiry and narrative identity. Participants aged 30 to 76 were interviewed and their experiences of living in an unstable economy that is dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Qualitative findings. The qualitative data provided a unique insight into the lives of youth in a town experiencing the stress of extreme economic volatility, with many youth showing awareness of boom-bust economic cycles (Höltge et al, 2021; Mahdiani et al, 2021; Theron et al, 2021). With regard to well-being, youth reported changes to their use of recreational spaces depending on their family’s financial situation, as well as shifts in their preferred career paths.…”
Section: The Resilient Youth In Stressed Environments (Ryse) Studymentioning
confidence: 99%
“…Qualitative findings. The qualitative data provided a unique insight into the lives of youth in a town experiencing the stress of extreme economic volatility, with many youth showing awareness of boom-bust economic cycles (Höltge et al, 2021; Mahdiani et al, 2021; Theron et al, 2021). With regard to well-being, youth reported changes to their use of recreational spaces depending on their family’s financial situation, as well as shifts in their preferred career paths.…”
Section: The Resilient Youth In Stressed Environments (Ryse) Studymentioning
confidence: 99%
“…For example, in research currently underway with two communities dependent upon the oil and gas industry as their major employer, my colleagues and I are documenting competing discourses concerning the resilience of these communities (Mahdiani et al, 2020). On the one hand, community leaders and vested government interests insist on the persistence of the oil and gas industry, maintaining that it should be supported through taxation policies that preserve the industry as it is, including abolishing requirements for more fuel-efficient cars and building pipelines to get more products to market.…”
Section: A Multi-systemic Understanding Of Resiliencementioning
confidence: 99%
“…This definition informs a new agenda for research, and one that is attentive to the promotive and protective mechanisms that support positive change at multiple systemic levels. For example, Mahdiani et al (2020) have shown that even in communities undergoing massive social disruption, as is occurring for communities dependent upon the oil and gas extraction and processing industries, sustainability is a reflection of each community's capacity to anticipate change and build the institutional responses that facilitate individual coping amid changes to economic conditions tied to the price of oil. It is studies like this that are driving greater interdisciplinarity in the field of resilience scholarship (a trend that is abundantly evident in this volume) and providing clues to the following questions: (1) How does the resilience of one system at one scale (e.g.…”
Section: Resilience As a Multi-systemic Conceptmentioning
confidence: 99%